Aspectos de implementação de mapas choropleth hierárquicos e interativos - LEAL, Marcos Senna Benaion (2019)
With the advent of concepts such as Big Data and Smart City the city and its population has generated a lot of data about sectors of society such as health, public transportation, basic sanitation, education, among others. However, this growing volume of data is little related to their demographic contexts, and when these data are represented by maps, they generally do not have the interactivity to explore this data, either by changing the study territory, increasing or decreasing its scope, relating other data for analysis, visually encoding a data, among other possibilities. Thus, this work aims to understand how to represent demographic data, more specifically how to represent data in geographic maps and how to make them interactive for the user, presenting as a final product a opensource software for visualizing hierarchical and interactive Choropleth geographic maps for the Web. To this end, the architecture, implementation methodology, technologies used, implementation aspects and the functionalities obtained are presented.